Evaluation of femoral head damage during canine total hip replacement - Wood, I.; Powell, H.; Kohm, A.; Lannutti, J. J.; Dyce, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Three types of hip skids and a Hohmann retractor technique were used to facilitate reduction of the prosthesis in cadaveric canine total hip replacement. The degree of damage to the femoral head was evaluated using scanning electron microscopy and optical profilometry. Standard metal and ME-92 coated metal hip skids caused severe regional scratching of the femoral head. Morphologically similar scratch patterns were also identified on femoral heads retrieved from clinical patients. Use of a plastic coated skid or the Hohmann retractor technique had no perceptible effect on surface finish, and therefore either method is acceptable in clinical practice. The use of metal hip skids cannot be recommended for hip reduction as the resultant pattern of femoral head scratching is likely to be associated with early and severe polyethylene wear.
Keywords: Hip skid; total hip replacement